Isolation and structure elucidation of two new flavonoid glycosides from the infusion of Maytenus aquifolium leaves. Evaluation of the antiulcer activity of the infusion - Vilegas, Wagner [UNESP]; Sanommiya, M.; Rastrelli, L.; Pizza, C. (Amer Chemical Soc, 1999)
Droplet countercurrent chromatography and high-performance liquid chromatography fractionation of the aqueous infusion from Maytenus aquifolium Martius leaves afforded two flavonoid tetrasaccharides: quercetin 3-O-alpha-L-rhamnopyranosyl(1-->6)-O-[beta-D-glucopyranosyl(1-->3)-O-alpha-L-rhamnopranosyl( 1-->2)-O-beta-D-galactopyranoside and kaempferol 3-O-alpha-L-rhamnopyranosyl(1-->6)-O-[beta-D-glucopyranosyl( 1-->3)-O-alpha-L-rhamnopyranosy(1-->2-2)-O-beta-D-galactopyranoside. All structures were elucidated by spectroscopic methods. Pharmacological essays of the infusion showed antiulcer activity in rats.
Keywords: Maytenus aquifolium Martius; Celastraceae; espinheira santa; infusion; antiulcer activity; flavonoid glycosides; 1D and 2D NMR